One-step synthesis of glycoprotein mimics in vitro: improvement of protein activity, stability and application in CPP hydrolysis. Issue 32 (28th July 2016) - Cui, Yuecheng; Li, Zhenhua; Wang, Lei; Liu, Feng; Yuan, Yuqi; Wang, Hongwei; Xue, Lulu; Pan, Jingjing; Chen, Gaojian; Chen, Hong; Yuan, Lin
Abstract : Glycoprotein mimics produced in vitro by one-step conjugation of glycopolymer and pyrophosphatase have improved bioactivity and stability for potential biomedical applications. Abstract : Glycopolymer–protein biomimetic materials have been receiving considerable attention in various biomedical and pharmaceutical studies and applications. However, owing to the easily induced inactivation of protein and the complexity of preparation, efficient in vitro synthesis of highly active and stable glycopolymer–protein conjugates is considerably difficult. Here, an ideal and facile one-step method using an analogue of N -acetyl-d -glucosamine (GlcNAc), the key unit of the universal biological polysaccharide, is proposed to prepare glycopolymer–protein conjugates with improved protein activity and stability. Inorganic pyrophosphatase (PPase) was conjugated through a one-step thiol-disulfide exchange reaction with a series of well-defined and molecular weight-controlled glycopolymers, poly(2-methacrylamido glucopyranose) (PMAG), prepared via reversible addition–fragmentation chain transfer (RAFT) polymerization. The results showed that the PMAG–PPase conjugate with a polymer chain of comparatively lower molecular weight (8.0 kDa) exhibited excellent ability to improve enzymatic activity by about 50%; it can maintain the activity at extreme pH and high salt concentration. The glycopolymer–protein conjugates also exhibited excellent resistance to both protease and glycosidase. Moreover, the glycopolymer–protein conjugates could efficiently catalyze the hydrolysis reaction of calcium pyrophosphate (CPP), exhibiting great potential in the treatment of the CPP deposition disease (CPDD). All the results revealed that the glycopolymer–protein materials described in this work, especially the conjugates with small molecular weight PMAG, possess significantly enhanced capacity to improve enzymatic activity, that the structure and property of PMAG play important roles in the tolerance of the conjugates to both environmental and biological stresses, and that the PMAG–PPase conjugate could potentially assist in the therapy of pseudogout. It can be predicted that this type of glycoprotein mimic will be favorable and valuable for applications in biological detection and clinical treatment.